Qualitative and quantitative analysis of alkaloid component in seeds from Peganum harmala L. extracts - Maeda H. Mohammad; Zaynab S. Abdulghany; Aous K. Al-mzaien (Iraqi Journal of Cancer and Medical Genetics, 2019)
Peganum harmala L. represents the major rich plant of alkaloids harmine and harmanline. In this study, one of these alkaloidswas detected qualitatively and quantitatively using different extraction methods: aqueous, methanol, and alkaloid. In comparisonbetween standard harmine and the three extracted using TLC technique, different spots were appeared from the three extractionmethods and the color looked like the standard. While when run the extracts on HPLC in comparison to standard harmine, threepeaks were observed and retention time of each extract was recorded to calculate the concentration of alkaloid. The best extractionmethod was the alkaloid extraction that give two peaks quite similar to that in the standard and almost the same retention time.This study shows that there are many important compounds in the alkaloid extraction of P. harmala of Iraqi species.